Before the Grand Opening : Measuring Washington State's Marijuana Market in the Last Year Before Legalized Commercial Sales. - Kilmer, Beau (RAND Corporation, 2013)
The 2012 passage of Initiative 502 in Washington state removed the prohibition on the production, distribution, and possession of marijuana for nonmedical purposes and required the state to regulate and tax a new marijuana industry. This report uses data from multiple sources to estimate the total weight of marijuana consumed in the state in 2013 to provide decisionmakers with baseline information about the size of the state's market.